Development of the creative personality of preschooler in the etnoculrutal environment - Nadiia Lazarovych (Vasyl Stefanyk Precarpathian National University, 2017)
In the article the state of problem of educational-educator process of children ofpreschool age is analysed in the field cultural environment. Importance of development ofcreative personality of preschool child is reasonable, influence of multicultural environmenton the capture of management creative activity general skills. Key words: gift, creative personality, culture, child, preschool age.